Patients With Diabetes Mellitus in Rural Area: Knowledge, Lifestyle, And Quality Of Life - MARISNA EKA YULIANITA; DEWI, CHITRA; ABD. RAHMAN (Althar Cendikia Education, 2023)
Indonesia is the fifth country with the highest number of Diabetes Mellitus (DM) sufferers in the world and is expected to reach 28.57 million in 2045. Diabetes Mellitus is a non-communicable disease that can affect anyone where knowledge, lifestyle and quality of life contribute to its incidence. the severity of the effects of the disease. The research objective was to determine knowledge, lifestyle, and quality of life of DM sufferers in rural areas. The design of this research is descriptive research. The sample of this study were 85 DM sufferers who were obtained using the technique purpossive sampling. Retrieval of data using Diabetes Knowledge Questionnaire (DKQ-24), Diabetes Self-Management Questionnaire (DSMQ), and WHOQOL-BREF. The results of this study indicate that the respondents' knowledge about diabetes mellitus is good (89.4%), the lifestyle of people with diabetes mellitus is good (87.1%), and the quality of life of people with diabetes mellitus is good (92.9%). This shows the knowledge, lifestyle and quality of life in diabetics is quite good. Based on the results of the study it was concluded that the knowledge, lifestyle and quality of life of DM sufferers were in the good category.